7 - Homage to ABDALLA BUJRA - Mahmood Mamdani (CODESRIA Bulletin, 2025)
I ﬁrst met Abdalla in 1973 at the University of Dar es Salaam, where he was professor of Sociology, and then at the CODES- RIA headquarters in Dakar, when he had become its new Executive Secretary following Samir Amin. Abdalla was a kind and modest man. His scholarship was outstanding. His main book focused on the Hadhramaut of South Yemen and the diaspora they spawned from the East African coast to Indonesia. Abdalla was a conscientious and hardworking Executive Secretary whose ﬁrst thought was how to make sure that CODESRIA would survive lean times. His solution was frugality, to save money to build an endowment, beginning by levying a ﬁnancial charge on all external funding received by the organisation. The matter came to a head after CODESRIA applied for the next round of funds. When donors carried out an audit, they discovered a pool of unspent money. Their ﬁrst impulse was to claim that this was evidence of corruption. But the charge would not stick because everyone knew Abdalla to be scrupulously honest. When asked, Abdalla said the money was saved with an eye on how CODESRIA could survive rainy days in the future. The donors demanded that the organisation be put under receivership, which would allow them to appoint a new management. In response, Abdalla turned to the membership for ideas on how to save the organisation’s independence.